2020
DOI: 10.3390/ijerph17186937
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Probabilistic Record Linkage with a Focus on Linkage Processing for WTC Registries

Abstract: Since its post-World War II inception, the science of record linkage has grown exponentially and is used across industrial, governmental, and academic agencies. The academic fields that rely on record linkage are diverse, ranging from history to public health to demography. In this paper, we introduce the different types of data linkage and give a historical context to their development. We then introduce the three types of underlying models for probabilistic record linkage: Fellegi-Sunter-based methods, machi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…The problem is to identify all the records belonging to each entity, and link them across the data sets. For instance 2 , discuss record linkage with reference to World Trade Center (WTC) registries.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is to identify all the records belonging to each entity, and link them across the data sets. For instance 2 , discuss record linkage with reference to World Trade Center (WTC) registries.…”
Section: Introductionmentioning
confidence: 99%
“…The second option is probabilistic record linkage that is based on a model to assess the discriminative power of each variable used in the record linkage strategy. The result is the probability that an entity in the first database is the same entity in the second database [5,6]. Several studies have demonstrated that in most cases, probabilistic approaches give better results than deterministic methods [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Record linkage uses deterministic or probabilistic approaches. [35][36][37][38] Experience from Brazil (a Portuguesespeaking country like Mozambique) 39 showed a high level of correlation for pair classification, but the probabilistic linkage retrieved links unidentified by the deterministic linkage. In the deterministic approach, a link is made if all fields agree.…”
Section: Methodsmentioning
confidence: 99%